Finite p-groups all of whose cyclic subgroups A, B with A ∩ B ≠ {1} generate an abelian group - Janko, Zvonimir (Israel journal of mathematics, 2013)
We characterize the title p-groups for all primes p.
Gesehen am 23.02.2018